Sob um olhar estrangeiro: a modernização do Japão nos escritos de Lafcadio Hearn (1890-1904) - Gonçalves, Edelson Geraldo (2017)
This study has as its object the unique process of modernization of Japan according to the writings of the Greek-Irish Lafcadio Hearn, author considered like one of the great western interpreters of Japan in the 19th century. In these writings will be sought the analysis of the modernization process of the Meiji Era (1868-1912), more precisely the conservative modernization carried out around the final two decades of that period. In order to reach such objectives, the writings (mainly books and letters) produced by the author in the time that he spent in Japan at the end of his life will be approached, searching for the impressions and conclusions that the author had about the country he encountered between the years of 1890 and 1904, that is, a nation in the process of modernization, undergoing rapid changes and finding a particular course for its modernity.